2012
DOI: 10.1159/000336513
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Regulation of Anti-Inflammatory Activities from Salivary Glands

Abstract: The cervical sympathetic nerves which innervate the medial basal hypothalamus-hypophyseal complex, primary and secondary lymph organs, and numerous glands, such as the pineal, thyroid, parathyroid and salivary glands form a relevant neuroimmunoendocrine structure that is involved in the regulation of systemic homeostasis. The superior cervical ganglia and the submandibular glands form a 'neuroendocrine axis' called the cervical sympathetic trunk submandibular gland (CST-SMG) axis. The identification of this ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 125 publications
(140 reference statements)
1
14
0
Order By: Relevance
“…The mechanism described here, where hypoxic upregulation of sialorphin results in transcriptional activation of Hif-1a and A2BR, may be restricted to CSM tissue, which under normal physiological conditions expresses high levels of vcsa1 relative to other tissues (15)(16)(17)(18). However, we have previously demonstrated that changes in expression of vcsa1 in rat corporal tissue are reflected by circulating levels of sialorphin in the blood (47).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism described here, where hypoxic upregulation of sialorphin results in transcriptional activation of Hif-1a and A2BR, may be restricted to CSM tissue, which under normal physiological conditions expresses high levels of vcsa1 relative to other tissues (15)(16)(17)(18). However, we have previously demonstrated that changes in expression of vcsa1 in rat corporal tissue are reflected by circulating levels of sialorphin in the blood (47).…”
Section: Discussionmentioning
confidence: 99%
“…2A, B, respectively). To further demonstrate the dependence of Hif-1a and a2br expression on sialorphin, we performed geneknockdown experiments using siRNA against vcsa1 (vcsa1-siRNA) in the CSM cells, which have been reported to have high levels of endogenous vcsa1 expression compared to other cell types (15)(16)(17)(18). Treating CSM cells with vcsa1-siRNA caused a significant decrease of ϳ50% Hif-1a and a2br expression ( Fig.…”
Section: Sialorphin Regulates Expression Of Hif-1a and A2br In A Dosementioning
confidence: 99%
See 1 more Smart Citation
“…Wounds in the oral cavity are repaired relatively easily, likely due to the involvement of saliva in oral tissue repair processes. Nevertheless, the described endocrine function of the salivary glands should not be disregarded as a possible mediator in oral tissue repair …”
mentioning
confidence: 99%
“…Nevertheless, the described endocrine function of the salivary glands should not be disregarded as a possible mediator in oral tissue repair. 1 Saliva is very important to oral health. A lack of saliva has been shown to bring serious problems to oral health, and delay the repair of mouth lesions.…”
mentioning
confidence: 99%